Diseño de una guia de educación sexual para estudiantes de noveno y decimo año de educación general básica del Colegio Particular Antonio Flores, ubicada en la provincia de Pichincha en la parroquia Calderón, en el periodo 2014 - 2015 - Toapanta Quishpe, Ángel Cristóbal (2015)
According this research, sexuality education in the educational system has been fragmented and scarce; the teacher has the obligation in self-prepared to resolve this problem, so also, the parents have different views created by the society, for this reason, the sexual education in teenagers is crossed out for the different ideologies. The students must learn complex and transcendental topics such as: communication, sexuality, puberty, values, to prevent in the youth in an orderly, logical and scientific manner, the consequences of a wrong way and irresponsible sexual practice, therefore, this research is important because it is focused on designing a sexual education guide to teach to the students in ninth and tenth year of basic education at Antonio Flores Private High School, becoming a fundamental tool in education and training in the sexual area due to the information has been obtained by several authors who specialize in this subject; this guide is designed to be used easily for teachers and they become transmitters of information to their students, searching for each topic will be innovative and motivational according to student’s needs, so that, they interact in the teaching-learning process and their knowledge will be more meaningful, during the application of each topic, it will get positive results with students and teachers in a close relationship with parents.